Peningkatan Kesejahteraan Rakyat Dalam Otonomi Daerah - Suparyadi - (Universitas Islam Indonesia, 2004)
The local autonomy as a great political product with high quality should be able to become the key to open the way out to overcome many kinds of problems of national economy such as national income, income per-capita proverty, unemployment and the event distribution of income. The local autonomy seen from the point of view of economy can mean the democratization of economy. It means the local government must be able to give the great opportunity of people to participate, to plane from the bottom leveling which it must be on the basis of the real need of the people, the potency of the local resources, the possession of rights and even the responsibility to make the people prosperous.The people economy in which most of the Indonesian people depend their life on it is in the oppressed condition because it lieson the lowest level in the national economy constellation. Even the Broad Outlines of the Nation's direction of 1999-2004 has mandated to the govemment to develop the people economy and the localautonomy has run for some years, in fact, the people economy is still not touched well by the existence of the local autonomy and the people economy development The purpose of the local autonomy, if it is analyzed more detailed, must be able to find many ways to improve the condition of the people economy.